Accumulation and distribution of neurotoxin BMAA in aquatic animals and effect on the behavior of zebrafish in a T-maze test. (15th January 2020) - Wang, Shuqin; Qiu, Jiangbing; Zhao, Mingyue; Li, Fangxiao; Yu, Rencheng; Li, Aifeng
Abstract: Neurotoxin β - N -methylamino- L -alanine (BMAA) has been widely detected in diverse aquatic organisms within different ecosystem trophic levels in recent years. It was the goal of this study to investigate the accumulation and tissue distribution of BMAA in marine opossum shrimp ( Neomysis awatschensis ) and freshwater zebrafish ( Danio rerio ) in exposure experiments. A T-maze test was tentatively adopted to assess the effects of BMAA on the learning and memory ability of zebrafish. Interestingly, N. awatschensis was testified to be capable of accumulating free soluble BMAA from bathing seawater through a biological filtration pathway (max. 110.6 μg g −1 wet weight). BMAA was transferred quickly from viscus to muscle and head tissues of zebrafish after intraperitoneal administration of 16.3 μg BMAA per individual twice in two weeks. BMAA accumulated mainly as the total soluble form in both experimental organisms. Results do not support the hypothesis that free BMAA molecules can be largely incorporated into protein in aquatic animals. Behavior of zebrafish in the T-maze test demonstrated that the short-term learning and memory ability was negatively impacted to some degree after three-days exposure to BMAA. Moreover, on Day 3, certain individual zebrafish exhibited freezing and loitering behavior. However, further investigation will be required to discern the long-term effects of BMAA on animals in order to evaluate the risk of BMAA exposure to human health. Highlights: Aquatic animals Neomysis awatschensis and Danio rerio were exposure to BMAA. N. awatschensis could accumulate soluble BMAA from seawater through filtration. Injected BMAA was transferred rapidly from viscus to muscle and head of zebrafish. BMAA could not be largely incorporated into protein in experimental animals here. BMAA can potentially impact spatial cognition and learning capacity of zebrafish.